Klasifikasi Tingkat Kepuasan Pengguna dengan Menggunakan Metode K-Nearest Neighbors (KNN) - Diansyah, Surya (Jurnal Sistim Informasi dan Teknologi, 2022)
Pekanbaru is one of the largest cities in Riau Province which is known as a civil city. Pekanbaru is also a city with a fairly high density of vehicles and causes a higher level of congestion. A sustainable transportation system can be a solution to current transportation problems and public transportation itself plays a role in providing effective and efficient transportation facilities for the community. The purpose of classifying the level of satisfaction of Trans Metro Pekanbaru bus users is to obtain knowledge and rules for the satisfaction level of Trans Metro Pekanbaru bus passenger services. The data processed in this study were 170 datasets sourced from questionnaires given to Trans Metro Pekanbaru bus passengers. Based on the data collection, what is done first is to find the optimal k value using the k-Fold Cross Validation method, while to find the classification of the level of service satisfaction of bus users using the K-Nearest Neighbor method. The results of the classification of the level of satisfaction of bus users using the k-nearest neighbor method are as many as 0 people who are very satisfied, 5 people are satisfied and 0 people are not satisfied with the services provided. Meanwhile, the accuracy level generated based on the test results has an accuracy rate of 94.12% with the optimal k value is k = 5. The results of this classification can be used as a reference for Trans Metro Pekanbaru buses for policies in Pekanbaru Trans Metro bus services.